Philosophy 167: Class 6 - Part 4 - Two New Sciences- an Overview. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Overview of Galileo's Discourses and Mathematical Demonstrations Relating to Two New Sciences.; Opening line: "That's the title page of the original, there are a lot of interesting things in it."; Duration: 10:23 minutes.; Segment: Class 6, Part 4.